Evaluasi dan Pengujian Internal Compatibility pada Aplikasi SIAKAD Universitas Sari Mulia - Halimatur Rahmi; Nor Anisa (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
The Academic Information System (SIAKAD) is a vital component in managing academic data at higher education institutions, including Universitas Sari Mulia. This study aims to evaluate the internal compatibility of the SIAKAD application, specifically the alignment and consistency of data across modules such as student profiles, course registration (KRS), academic grades, attendance, and payment. The primary issue addressed is the potential for data mismatches between modules, which could affect academic processes and user trust. This research employs a qualitative approach using the black-box testing method to assess the application's technical performance based on predefined test scenarios, alongside questionnaires to evaluate user experiences. The testing results demonstrate that all features, including login, profile management, attendance, grading, and payment, functioned as expected according to the test scenarios. Based on responses from 18 participants, 72.22% of users found the application easy to use and consistent in displaying data, though some features were deemed less optimal (5.56%). This study concludes that the SIAKAD application at Universitas Sari Mulia effectively supports academic data management, but further development is needed to improve feature quality and user satisfaction.